Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 292681 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Plantae", "Country is India" ] } The dataset includes 292681 records from 180 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001538-150504100648427/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences